Pelatihan Penulisan Artikel Ilmiah Berbasis Proses Bagi Mahasiswa - Amnie, Erlida; Ekaputra, Firdiawan; Nur Ismiatun, Asih (Pendidikan Sejarah FKIP Universitas JAMBI, 2025)
Writing scientific articles is a fundamental skill that needs to be practiced from the beginning of college. First-semester students generally do not have direct experience in writing scientific articles. This community service activity aims to provide training in scientific article writing to first-semester students of the Physics Education Study Program through a gradual approach and continuous mentoring. The implementation method is carried out in four stages, namely preparation with the completion of an initial perception questionnaire, implementation of training with structured mentoring for five weeks, completion of articles with the completion of a final perception questionnaire, and descriptive data analysis. The training material covers the structure of scientific articles using the IMRAD format (Introduction, Methods, Results, and Discussion) with a writing strategy that starts from the methods, results, discussion, conclusion, introduction, and abstract sections. The results of the initial perception survey showed that students already had conceptual knowledge about scientific articles but lacked direct experience. The final perception survey, completed after the training, showed a shift in students' orientation from passive knowledge to active experience. This was marked by an increase in procedural understanding, confidence, and motivation to write scientific articles. This activity successfully bridged first-semester students to enter the academic culture in a more conscious and reflective manner through the experience of writing a complete article.